Моделювання чорнометалургійних та лісохімічних процесів за матеріалами Північної експедиції - Готун, I.A.; Петраускас, A.B.; Петраускас, О.В. (Археологія, 2005)
Другу статтю з циклу публікацій про експериментальні студії Північної експедиції ІА НАН України присвячено результатам дослідів з добування болотної руди, спорудження металургійного горна, агломераційної печі, смолокурні, виготовлення міхів та моделювання збагачення залізної руди, крично-рудного процесу, випалювання деревного вугілля, смолокуріння та вигонки дьогтю ямним і корчажним способами. Статья, продолжающая цикл публикаций об экспериментах в рамках работы Северной экспедиции ИА НАН Украины, посвящена результатам опытов в отрасли черной металлургии и лесохимических промыслов. Описаны основания для натурного моделирования сооружений, процессов и технологий, а также ход и результаты самих экспериментов. Проанализированы средневековые добыча и обогащение руды, получение кричного железа, выжигание древесного угля, смолокурение и возгонка дегтя ямным и корчажным способами, а также результаты экспериментов в этом направлении. Охарактеризованы археологические прототипы натурных реконструкций. This article continuing a series of publications about the experiments undertaken by the Northern expedition from the Institute of Archaeology of the National Academy of Sciences of Ukraine is devoted to the experimental results in the sphere of ferrous metallurgy and wood-chemical crafts. The grounds for full-scale modeling of the buildings, processes and technologies, course and the results of the experiments proper are described. Medieval extraction of ore and dressing treatment, production of bloomery iron, wood charcoal burning, extraction of tar and its sublimation in pits and korchagas (large earthenware pots), as well as experimental results in this field are analyzed. Archeological prototypes for the full-size reconstructions are characterized.